2005
DOI: 10.5694/j.1326-5377.2005.tb06671.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of overseas commercial kidney transplantation: an Australian perspective

Abstract: Lack of donors has led to a worldwide increase in commercial kidney transplantation programs where recipients acquire kidneys either from executed prisoners or live non‐related donors. Commercial transplantation is prohibited by legislation in Australia. Our centres have had 16 patients who have travelled overseas to receive a commercial kidney transplant; five have subsequently died. As has been found previously, patients who received commercial transplants were more likely to develop infections such as HIV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 16 publications
4
45
0
1
Order By: Relevance
“…According to Kennedy and colleagues, 5 patient of 16 died during the course of overseas KT, and concluded that the patient and graft survival were worse than KT within Australia (4). Similar concern was raised concerning LT, where 1 and 5 yr survival rate was lower among overseas LT recipients (90% and 77% vs 93% and 93%) (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kennedy and colleagues, 5 patient of 16 died during the course of overseas KT, and concluded that the patient and graft survival were worse than KT within Australia (4). Similar concern was raised concerning LT, where 1 and 5 yr survival rate was lower among overseas LT recipients (90% and 77% vs 93% and 93%) (14).…”
Section: Discussionmentioning
confidence: 99%
“…Alghamdi reported that overseas KT patients had a higher percentage of acute rejection compared to the patients transplanted within Saudi Arabia (27.9% vs 9.9%, P = 0.005) (17). Others have described a higher rate of fungal, CMV, HIV, or hepatitis B or C infection, or urological complication among overseas KT recipients (4, 9, 15-18). According to our data, KT recipients experienced a relatively high postoperative complication rate of 42.5%, with infection as the most common cause.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is fraught with both clinical and public health implications. Apart from the standard of hygiene and quality of postoperative care in overseas centers, recipients have been reported to have contracted infections endemic to overseas centers (e.g., tuberculosis, aspergillus, and hepatitis B) or even donor malignancies [2931]. Medical records from overseas centers are often incomplete, scant, in a foreign language, or unobtainable [29, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the standard of hygiene and quality of postoperative care in overseas centers, recipients have been reported to have contracted infections endemic to overseas centers (e.g., tuberculosis, aspergillus, and hepatitis B) or even donor malignancies [2931]. Medical records from overseas centers are often incomplete, scant, in a foreign language, or unobtainable [29, 32, 33]. Fatal postoperative bleeding has also been reported, as have both under or over-immunosuppresion, and infection with the HIV virus [29, 30, 32, 34, 35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation